Professional Skills Requirement of Mechanical Engineers. (December 2019) - Ismail, W Omar Ali Saifuddin Wan; Hamzah, Noraini; Fatah, Ireana Yusra Abdul; Zaharim, Azami
Abstract: Professional Skills is the basic requirement that all engineers need to master in the current job market. This study was conducted throughout peninsular Malaysia using the Soft Skills Model introduced by the Ministry of Education (MoE). Among the objectives of this study is the level of requirement of the Soft Skills (SS) element to produce a competitive Mechanical Engineer and identify the most dominant Soft Skills needed in the current job market against Mechanical Engineers. The questionnaire distributed to respondents and data was analysed using XL-STAT 2014 software to obtain Discriminant Analysis (DA) to achieve the objective of the study. The overall percentage for (SS) elements is 91% respectively. This study will be a complementary set for the students of Mechanical Engineering in Malaysia. Mastering the features required by the industry makes it easy for students to put themselves in the real job world.